Influence of electron irradiation on the structure evolution and creep of Zr1Nb alloy at 380 °C - Karaseva, E.V.; Malykhin, S.V.; Mats, A.V.; Mats, V.A.; Savchuk, E.S.; Sokolenko, V.I. (Вопросы атомной науки и техники, 2021)
The effect of electron irradiation on the evolution of the structure and creep of the samples Zr1Nb alloy of industrial production and samples obtained by the IPD method were studied. It was shown that irradiation with electrons with a dose not exceeding D = 5∙10¹⁹ сm⁻² does not affect the plastic deformation mechanisms of the industrial Zr1Nb alloy, as a result of which its high thermomechanical and radiation stability is maintained. Irradiation by electrons with an energy of E = 10 MeV and doses of D = 6∙10¹⁷ and 5∙10¹⁹ сm⁻² does not change the character of the deformation nanostructure of the Zr1Nb alloy, but initiates return processes in grain boundaries and boundary regions and cause the changes in crystalline anisotropy of GPU lattice, which leads to softening of the material during creep at 380 °C. Вивчено вплив електронного опромінення на еволюцію структури та повзучість сплаву Zr1Nb промислового виробництва і отриманого методом ІПД. Показано, що опромінення електронами з дозою, яка не перевищує D = 5∙10¹⁹ см⁻², не впливає на механізми пластичної деформації промислового сплаву Zr1Nb, внаслідок чого зберігається його висока термомеханічна та радіаційна стійкість. Опромінення електронами з енергією E = 10 МеВ і дозами D = 6∙10¹⁷ і 5∙10¹⁹ см⁻² не змінює характер деформаційної наноструктури сплаву Zr1Nb, але ініціює зворотні процеси в межах зерен і приграничних областях, викликає зміни кристалічної анізотропії ГПУ-ґратки, що призводить до знеміцнення матеріалу в процесі повзучості при 380 °С. Изучено влияние электронного облучения на эволюцию структуры и ползучесть сплава Zr1Nb промышленного производства и полученного методом ИПД. Показано, что облучение электронами с дозой, не превышающей D = 5∙10¹⁹ см⁻², не влияет на механизмы пластической деформации промышленного сплава Zr1Nb, вследствие чего сохраняется его высокая термомеханическая и радиационная устойчивость. Облучение электронами с энергией E = 10 МэВ и дозами D = 6∙10¹⁷ и 5∙10¹⁹ см⁻² не изменяет характер деформационной наноструктуры сплава Zr1Nb, но инициирует возвратные процессы в границах зерен и приграничных областях, вызывает изменения кристаллической анизотропии ГПУ-решетки, что приводит к разупрочнению материала в процессе ползучести при 380 °С .